Kunstwandeling : Kortrijk Vlaandert. - Van Canneyt, Hilde; Lesage, Geert; Haghebaert, Stijn; Seynaeve, Kristian; van Hove, Hans; Kortrijk (Kortrijk : Kortrijk Vlaandert vzw, 2013)
De Cupere, Peter ; Vanmechelen, Koen ; Berkvens, Elise ; Van Severen, Hannes ; Boogaerts, Line ; Muller, Fien ; Baelen, Steven ; Woestenborghs, Tom ; Vandeghinste, Ruben ; Ervinck, Nick ; Coucke, Joachim ; et al.
op verschillende locaties in Kortrijk, 07/07-18/08/2013
kunstcatalogus